Richard Nixon : The Life - Farrell, John A. (London SCRIB, 2018)
Analyzes the circumstances of Pres. Richard Nixon's life in an effort to define his underlying motivations.
Include Index, Illustration and Acknowledgment
Keywords: United States -- Politics and government -- Presidents